2000
DOI: 10.1046/j.1440-1754.2000.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of childhood abdominal pain in an Australian general practice

Abstract: Abdominal pain remains a common problem of children attending an Australian general practice, and was associated with features suggesting that it is related to anxiety and coping ability. Abdominal pain is not usually associated with disease; most families recognize this and cope with abdominal pain without medical consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 24 publications
3
42
3
1
Order By: Relevance
“…Recurrent abdominal pain was found to be associated with major negative life events, 47 daily stressors, 51 anxiety, 52 and sleep disturbances. 53 This study is unable to clarify the reasons for the increase in prevalence, but it seems evident that children's living environments and lifestyles were less favorable in this respect in 1999 than in 1989. An alarming finding was that, even in cases in which a child reported having headaches or abdominal pain almost daily, many parents (14% for headaches and 30% for abdominal pain) reported that their child never had these symptoms.…”
Section: E438mentioning
confidence: 88%
“…Recurrent abdominal pain was found to be associated with major negative life events, 47 daily stressors, 51 anxiety, 52 and sleep disturbances. 53 This study is unable to clarify the reasons for the increase in prevalence, but it seems evident that children's living environments and lifestyles were less favorable in this respect in 1999 than in 1989. An alarming finding was that, even in cases in which a child reported having headaches or abdominal pain almost daily, many parents (14% for headaches and 30% for abdominal pain) reported that their child never had these symptoms.…”
Section: E438mentioning
confidence: 88%
“…[10][11][12][13] Still, research on consultation patterns for pediatric FSS remains scarce. The prevailing research data indicate that even though many parents cope with their child' s symptoms without resorting to medical care, [14][15][16] children' s use of general practitioner services has increased in particular in North European countries. 17 Suggested explanations for this trend include higher parental awareness and increases in both chronic disease and FSS among children in general.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage corresponds to percentages reported in other population-based studies on children and adolescents with chronic benign (ie, functional) pain. 14,30 Three patterns of factors associated with medical consultations due to FSS in children aged 5 to 7 years were seen. First, consulters more often had parents who both were not native Danish compared with nonconsulters.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in an Australian general practice among children in the waiting room reported that 44% of the children experienced abdominal pain in the preceding 12 months, of whom 12% experienced abdominal pain at least once each month. 17 Our research group recently showed that primary care physicians are routinely confronted with children with abdominal pain. 2 Thus, data on the prevalence and incidence of CAP among children visiting primary care with abdominal pain are valuable.…”
Section: Discussionmentioning
confidence: 99%